Wetting Boundary Condition in an Improved Lattice Boltzmann Method for Nonideal Gases (Communications in Computational Physics, 2020)
A numerical scheme capable of modeling fluid behavior on wetting surfacesis developed based on an interface-capturing lattice Boltzmann equation model [Q.Lou and Z. Guo, Phys. Rev. E 91, 013302 (2015)], which has not yet been applied towetting problems. With the proposed numerical scheme, the spurious densities nearthe solid surfaces can be eliminated and a wide range of equilibrium contact angles canalso be reproduced. Further, the equilibrium contact angle on the solid surface, as asimulation parameter, can be given in advance according to the wettability. Numericaltests, including the dynamics behavior of a liquid drop spreading on a smooth surfaceand the capillary intrusion, demonstrate that the proposed numerical scheme performswell and can eliminate the spurious densities near the solid surface.